Strategic information for hospital service planning: A linked data study to inform an urban Aboriginal Health Liaison Officer program in Western Australia - Katzenellenbogen, J.; Miller, L.; Somerford, Peter; McEvoy, S.; Bessarab, Dawn (CSIRO, 2015)
Objectives The aim of the present study was to provide descriptive planning data for a hospital-based Aboriginal Health Liaison Officer (AHLO) program, specifically quantifying episodes of care and outcomes within 28 days after discharge. Methods A follow-up study of Aboriginal in-patient hospital episodes was undertaken using person-based linked administrative data from four South Metropolitan hospitals in Perth, Western Australia (2006-11). Outcomes included 28-day deaths, emergency department (ED) presentations and in-patient re-admissions. Results There were 8041 eligible index admissions among 5113 individuals, with episode volumes increasing by 31% over the study period. Among patients 25 years and older, the highest ranking comorbidities included injury (47%), drug and alcohol disorders (41%), heart disease (40%), infection (40%), mental illness (31%) and diabetes (31%). Most events (96%) ended in a regular discharge. Within 28 days, 24% of events resulted in ED presentations and 20% resulted in hospital re-admissions. Emergency readmissions (13%) were twice as likely as booked re-admissions (7%). Stratified analyses showed poorer outcomes for older people, and for emergency and tertiary hospital admissions. Conclusions Future planning must address the greater service volumes anticipated. The high prevalence of comorbidities requires intensive case management to address case complexity. These data will inform the refinement of the AHLO program to improve in-patient experiences and outcomes. What is known about the topic? The health gap between Aboriginal and non-Aboriginal Australians is well documented. Aboriginal people have significantly higher hospital utilisation rates, as well as higher rates of complications, comorbidities and discharges against medical advice (DAMA). Aboriginal patients receive most of their specialist services in hospital; however, detailed person-based analyses are limited and planning is often based on crude data. What does this paper add? This is the first analysis of linked data focusing on Aboriginal patient flows and volume and 28-day health system outcomes following hospital admission for all causes in a large metropolitan setting. Because the data were linked, admissions belonging to a single episode of care were combined, ensuring that transfers were not counted as re-admissions. Linkage also allowed follow up across time. The results highlight the main disease groups for which Aboriginal patients are admitted, how this varies by age and the high proportion of patients returning to (any) hospital within 28 days, either through EDs or as booked (pre-arranged) admissions. These data aid in the planning of hospital-based Aboriginal health liaison services. What are the implications for practitioners? The paper outlines the complexity with which many Aboriginal patients present to hospital and the risk of DAMA and re-admission. Clinical and organisational strategies can be put in place in hospitals to address these risks and ensure improved continuity of care with community-based primary health services. The Western Australian South Metropolitan Health Service is reviewing these data and will monitor the impact of the hospital-based AHLO program.